Identifikasi Penyebab Kerusakan pada Alat Pemadam Kebakaran di KM. Lambelu Serta Dampaknya Terhadap Keselamatan - Ode Rahan Viardhana; Arleiny Arleiny; Teguh Pribadi; Upik Widyaningsih (JURAL RISET RUMPUN ILMU TEKNIK, 2025)
Shipping safety is everything that can be developed related to accident prevention measures when carrying out work in the shipping sector. Shipping safety and security is a state of fulfillment of transportation safety and security requirements in waters, ports and maritime environments. Fire extinguishing equipment is vital in ensuring operational safety on board and meeting the requirements set by SOLAS. Regular and regular maintenance is required to ensure that fire extinguishing equipment is always in a ready-to-use condition in the event of an emergency. Conducting periodic drills aims to find out the extent of the readiness of fire extinguishing equipment to be used and its completeness. This study has the purpose of finding out: 1) Factors causing fire extinguishing equipment in KM. Lambelu is less than optimal 2) The impact that will occur if routine maintenance is not carried out on the fire extinguisher. The method used by the researcher this time is a qualitative descriptive method. The results of this study are as follows, The main causes of damage to light fire extinguishers in KM. Lambelu is the lack of inspection and supervision that is carried out periodically on the equipment, while other supporting factors are the lack of understanding and skills of the crew in operating light fire extinguishers, the use of light fire extinguishers that are not in accordance with the SOPs, and exposure to the marine environment that causes light fire extinguishers to corrode or rust. The impact of not carrying out routine maintenance is a decrease in preparedness in times of emergency, in addition to that it will cause financial losses, operational disruptions, and reduce public trust in the company.